DESIGN AND BUILD AN ONLINE RESERVASTION SYSTEM FOR HEALTH SERVICES AT PET CLINICS USING THE PRIORITY SCHEDULING ALGORITHM - Rumampuk, Viola Gracella; Ardiansyah, Rizka; Joefrie, Yuri Yudhaswana; Laila, Rahmah; Pusadan, Mohammad Yazdi (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
The limited number of veterinarians and the absence of an online reservation service at Louis Pet Shop Palu, which requires prospective patients or customers to come in person to take a queue number and wait to receive medical services. The long queues that often occur cause inconvenience and waste of time for customers. In addition, the mismatch of schedules with customer preferences adds to the inconvenience, which can result in customer dissatisfaction and potential losses for the clinic as customers seek services elsewhere that are more convenient. This research uses the Black Box testing method to ensure the smooth running of the created program. In conclusion, this problem can be overcome by building an online reservation information system that integrates a priority-based queue management mechanism. The implementation of this feature uses Priority Scheduling Algorithm combined with WhatsApp Gateway as a reminder.